The network of Shanghai Stroke Service System (4S): A public health-care web-based database using automatic extraction of electronic medical records. Issue 5 (July 2018) - Dong, Yi; Fang, Kun; Wang, Xin; Chen, Shengdi; Liu, Xueyuan; Zhao, Yuwu; Guan, Yangtai; Cai, Dingfang; Li, Gang; Liu, Jianmin; Liu, Jianren; Zhuang, Jianhua; et al.
Background: Several stroke outcome and quality control projects have demonstrated the success in stroke care quality improvement through structured process. However, Chinese health-care systems are challenged with its overwhelming numbers of patients, limited resources, and large regional disparities. Aim: To improve quality of stroke care to address regional disparities through process improvement. Method and design: The Shanghai Stroke Service System (4S) is established as a regional network for stroke care quality improvement in the Shanghai metropolitan area. The 4S registry uses a web-based database that automatically extracts data from structured electronic medical records. Site-specific education and training program will be designed and administrated according to their baseline characteristics. Both acute reperfusion therapies including thrombectomy and thrombolysis in the acute phase and subsequent care were measured and monitored with feedback. Primary outcome is to evaluate the differences in quality metrics between baseline characteristics (including rate of thrombolysis in acute stroke and key performance indicators in secondary prevention) and post-intervention. Conclusions: The 4S system is a regional stroke network that monitors the ongoing stroke care quality in Shanghai. This project will provide the opportunity to evaluate the spectrum of acute stroke care and design quality improvement processes for better stroke care. A regional stroke network model for quality improvement will be explored and might be expanded to other large cities in China. Clinical Trial Registration-URL: http://www.clinicaltrials.gov . Unique identifier: NCT02735226.